Optical confirmation of biaxial nematic (Nb) phase in a bent-core mesogen - VIJ, JAGDISH; PANOV, VITALI (My University, 2009)
A bent-core mesogen with different end groups has been studied for different surface conditions in both planar and homeotropic cells using techniques for measuring biaxiality and optical switching. Biaxial nematic phase observed in between the uniaxial nematic and smectic phases is evidenced by a sharp increase in the biaxiality in a homeotropic cell measured using a photoelastic modulator. The material in this phase is switchable through the minor director with an in-plane electric field. In a planar cell, a step in the difference in the refractive indices resulting from the uniaxial to biaxial transition is also observed.
PUBLISHED
Keywords: 10